BIOMONITORING PENCEMARAN AIR MENGGUNAKAN SIPUT (GASTROPODA) - Karmila Fajriah; Herliana; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
Snails (Gastropods) are aquatic organisms that interact directly with their environment and are sensitive to changes in water quality. Their biological characteristics, such as low mobility and the ability to accumulate pollutants, make them effective bioindicators for detecting water pollution. This study aims to analyze the role of snails as bioindicators of water pollution using a literature review method based on recent national and international scientific references. The results show that snails can indicate water contamination, especially due to heavy metals such as lead (Pb), cadmium (Cd), and mercury (Hg), through bioaccumulation processes. In addition, changes in the abundance and diversity of snails reflect environmental conditions, where a decrease in population and dominance of certain species indicate polluted waters. Therefore, snails can be effectively used as bioindicators in water pollution biomonitoring.Keywords: bioindicator, snails (Gastropods), soil pollution.